What matters to travel bloggers before the trip? the Malaysian travel blogger and tourist perspective - Wan Abdul Rahman, Nik Alia Fahada; Mohamed, Monizaihasra; Sulong, Farizah; Rosnon, Mohd Roslan; Che Mohd Hashim, Azreen Jihan (Human Resource Management Academic Research Society, 2019)
Social media, particularly travel blog are increasingly relevant in tourism practices affecting destination and business. With the growth of internet-based social media technologies, tourists are able to communicate, interact and establish relationship with destinations, business and other tourists. Pre-visit stage of tourist experience involves activities that focused on travel planning, in which travel blogs is considered as a rich sources of travel information. Through interviewing 19 travel bloggers, this study aims to understand travel bloggers behavior and strategies at the pre-visit stage of tourist experience. The findings show that, travel bloggers engage with travel blogs with different behavior which influenced by different motivations. It is also highlighted that interaction in blogosphere serves an important role in influencing travel bloggers engagement with travel blogs before the travel. The implication of the study and suggestion for future research are explained.